Correlation between cervical infection and preterm labor - Larisa Mešić Ðogić; Nenad Lučić; Dragana Mićić; Feđa Omeragić; Enes Hodžić; Seid Fazlagić; Refka Kovač; Nevenka Pavlović (Medicinski glasnik, 2017)
Aim: To investigate a correlation between cervical canal infection and imminent preterm labor and to identify most frequent pathogens. Methods: A prospective study was conducted in obstetrics/gynecology departments of Health Center and the University Clinical Center Tuzla, and General Hospital Tešanj (Bosnia and Herzegovina, B&H) between October 2013 and May 2014. An examined group included 50 healthy pregnant women with singleton pregnancy of the gestation age between the 28th and 37th week, with cervical changes that are related to imminent preterm labor. Changes were detected by ultrasound biometry of cervix and modified Bishop score. A control group included 30 healthy pregnant women with singleton pregnancy of the gestation age between the 28th and 37th week of pregnancy without signs of imminent preterm labor. Cervical mucus was microbiologically analyzed for identification of pathogens. Results: The infection in cervical canal was proven in 35 (70%) examinees and four (13%) patients from the control group (p=0.015). In seven (20%) cases each Ureaplasma and Mycoplasma were detected followed by E. coli in five (14%) cases (p=0.001). Conclusion: Cervical canal infection is associated with changes on cervix and premature rupture of fetal membranes, i.e. preterm labor and imminent preterm labor. Screening for infection before pregnancy should be the main task of family doctors as well as gynecologists.
Keywords: uterine cervicitis; premature birth; pregnancy complication